Visions of the Blue God: A Note on Composition (and Performance?) in Bhāgavata Purāṇa Illustrations. (27th September 2018) - Ehnbom, Daniel
Abstract: This note examines images of textual narration in sixteenth- and seventeenth-century Indian manuscript illustration. In examining a large, dispersed Tenth Book of the Bhāgavata Purāṇa (Delhi–Agra Region [Mathura?] c. 1520–30 CE) that is the earliest surviving illustrated version of the life of Krishna as recounted in the Tenth Book, the author distinguishes between representation of the sage Śuka reciting the text and non-brāhmaṇical recitation of the text as depicted within the illustrations. He suggests that these depictions, coupled with the sudden appearance of lively and varied compositions in a painting style generally associated with formal, even hieratic, compositions, may link the illustrations to a tradition of performance of the Kṛṣṇa story emerging in the sixteenth century in connection with the Vallabhite revival of Kṛṣṇa worship. This performance tradition is otherwise known only through textual references.